Survival of dental implants placed in autogenous bone grafts and bone flaps in head and neck oncology patients: a systematic review - Dominic P. Laverty; Robert Kelly; Owen Addison (SpringerOpen, 2018)
Abstract Using implants to retain prostheses as part of the oral rehabilitation of head and neck cancer patients is an increasingly common treatment modality, particularly in transported bone which is used to reconstruct defects following oncological surgical resection. The aim of this systematic review is to evaluate the survival of dental implants placed into autogenous bone grafts and flaps, in head and neck cancer patients. MEDLINE, EMBASE, CENTRAL and Science Direct databases were searched (1980-August 2017) for studies evaluating intra-oral implant placement into autogenous bone grafts and flaps in H&N cancer patients. Twenty articles were included reporting on 1905 implants placed into autogenous bone in head and neck cancer patients. Implant survival varied from 54 to 100% within the studies with 11 studies reporting implant survival of over 90%. In conclusion, intra-oral implant survival in autogenous bone grafts in head and neck oncology patients is promising, however inconsistencies in data reporting and in outcome definitions precludes formal meta-analysis.